Water resources managment: rural community participation at catchment level in Malawi. - Chunga, Brighton Austin (Cranfield University, 2019)
Water resources in sub-Saharan Africa region, like other regions in the world, are heavily affected by the impacts of climate change, pollution and population growth. Water management practices recognise the need for ‘stakeholder’ participation. Participation forms part of principles of water management concepts such as Integrated Water Resources Management and Water Governance. Most governments have reformed its policies and legislation to include the participatory principle. The rationale for the principle of participation is the apparent evidence that water has a broad spectrum of users and uses which are mostly competing. Research has however shown that stakeholders, especially rural communities, are not adequately engaged. Current community engagement has mainly targeted water point’s maintenance and sanitation. Little is known on the failure of engaging rural communities in managing water resources in the catchments. This research used a qualitative case study to explore rural community engagement in water resources management at the catchment level. Fieldwork was conducted in three catchments: Linthipe, South Rukuru and South West Lakeshore in Malawi. It confirmed the reports that rural communities are not engaged as expected. It found out that one of the main reasons for non-participation is the poor engagement mechanism. It identified several factors (24 barriers) which limit the participation of rural communities. It also found that a cause-effect relationship exists between the factors. The research argues that such detailed analysis of cause-effect of the factors provides several options to policymakers and practitioners in addressing challenges affecting engagement in water resources management. Further, the research proposed the framework which would improve existing engagement mechanisms for rural communities in Malawi. The framework will also help implement catchment management activities for the newly established National Water Resources Authority.
Keywords: Catchment management; IWRM; policy; stakeholder engagement; water governance; analysis cause and effect